MUSEUM LIGHTING: STRATEGIES, TECHNOLOGIES, AND IMPACT ON EXHIBITS - Radi Ivanov Zahariev (International Journal of Innovative Technologies in Social Science, 2025)
Museum lighting plays a critical role in shaping the visitor experience while ensuring the preservation of sensitive artifacts. Unlike standard lighting systems, museum lighting must balance aesthetics, functionality, and conservation. This paper explores the fundamental principles, lighting strategies, and advanced technologies used in museum environments. It examines case studies from major museums, evaluates the benefits of LED technology, and highlights the role of intelligent lighting systems. The findings underscore the importance of integrated lighting design in safeguarding cultural heritage while enhancing curatorial expression. In addition, the paper contextualizes lighting as an architectural and phenomenological tool that bridges perception, emotional resonance, and conservation ethics.